Absence of Asymptomatic Malaria Reservoirs in an Area with a Previous History of Local Malaria Transmission: A Successful Experience in Line with the Malaria Elimination Program in Iran - Zainab Hosseini; Kourosh Azizi; Mohsen Moghadami; Mehdi Hassaniazad; Reza Shafiei; Habibollah Turki (Journal of Arthropod-Borne Diseases, 2023)
Background: Asymptomatic malaria is a major challenge to be addressed in the implementation of the malaria elimination program. The main goal of the malaria surveillance system in the elimination phase is to identify reliably all the positive cases of malaria reliably (symptomatic and asymptomatic) in the shortest possible time. This study focused on the monitoring of asymptomatic malaria reservoirs in areas where local transmission had been previously established.